2015
DOI: 10.1007/s40891-015-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Performance of Tire Crumbles with Fly Ash and Kaolin Clay

Abstract: In this study, the impact of tire crumbles as an admixture on compaction and strength behavior of two different materials, kaolin clay and fly ash is considered. In order to understand the compaction and strength behavior, proctor compaction tests and California bearing ratio (CBR) tests respectively were performed on the mixture of clay and fly ash with tire crumbles. Test results have shown that maximum dry unit weight decreases when tire crumbles are added in fly ash or clay. Increment in the optimum moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The reductions reported for the OMC have been mainly ascribed to the TDA material's hydrophobic character and hence its lower water adsorption-retention capacity (being mainly less than 4%) compared with that of the fine soil particles, particularly clays [16]. It should be mentioned that, while the reported results for the MDUW are fairly consistent, a limited number of studies have reported either negligible or increasing trends for the OMC with respect to increasing the TDA content [42][43][44]. These unexpected trends may be attributed to TDA segregation (and hence TDA clustering) effects caused by inadequate soil-TDA mixing during sample preparation for the compaction test [19,39].…”
Section: Governing Mechanisms Controlling the Compactability Of Soil-tda Blendsmentioning
confidence: 94%
“…The reductions reported for the OMC have been mainly ascribed to the TDA material's hydrophobic character and hence its lower water adsorption-retention capacity (being mainly less than 4%) compared with that of the fine soil particles, particularly clays [16]. It should be mentioned that, while the reported results for the MDUW are fairly consistent, a limited number of studies have reported either negligible or increasing trends for the OMC with respect to increasing the TDA content [42][43][44]. These unexpected trends may be attributed to TDA segregation (and hence TDA clustering) effects caused by inadequate soil-TDA mixing during sample preparation for the compaction test [19,39].…”
Section: Governing Mechanisms Controlling the Compactability Of Soil-tda Blendsmentioning
confidence: 94%
“…Various tests for tyre chips has been carried in laboratory such as water absorption, tensile strength, compression and Specific gravity. For carrying the test with soft clay, various comparative study has been made through the existing researches and experiments [9].Thus the usage of tyre chips not only reduces the waste but it also helps in saving the natural resources, energy and to increase the stability of soft soil [1]. Water absorption of tyre chips 4%…”
Section: Clayey Soilmentioning
confidence: 99%
“…In the present study, the shredded rubber tyre is selected as an additive and randomly mixed with the soil for 0%, 5%,10%, and 15% by weight of soil. The % of rubber content is decided on the basis of previous studies (22,25,27,31,33,34,36) . The strength characteristics and swelling potential of treated soil are examined by performing the Unconfined compression strength test, CBR test, and Swelling pressure test respectively.…”
Section: Mixing Proportionsmentioning
confidence: 99%